2014
DOI: 10.1111/1758-2229.12230
|View full text |Cite
|
Sign up to set email alerts
|

A severe reduction in the cytochrome C content of Geobacter sulfurreducens eliminates its capacity for extracellular electron transfer

Abstract: The ability of Geobacter species to transfer electrons outside the cell enables them to play an important role in a number of biogeochemical and bioenergy processes. Gene deletion studies have implicated periplasmic and outer-surface c-type cytochromes in this extracellular electron transfer. However, even when as many as five c-type cytochrome genes have been deleted, some capacity for extracellular electron transfer remains. In order to evaluate the role of c-type cytochromes in extracellular electron transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 69 publications
2
50
0
Order By: Relevance
“…This is possible owing to the high abundance of c‐ type cytochromes (more than 100 genes encode these redox proteins), most of which contain multiple heme groups that can act as electron transfer mediators and are exposed on the outermost membrane of the cell . Moreover, the culture of heme‐depleted cells has recently revealed that c‐ type cytochromes are the key for the interchange of electrons with an electrode . Therefore, the redox chemistry of Geobacter is mainly based on the chemistry of the heme group, which hosts an iron atom that can be reversibly reduced or oxidized.…”
Section: Introductionmentioning
confidence: 99%
“…This is possible owing to the high abundance of c‐ type cytochromes (more than 100 genes encode these redox proteins), most of which contain multiple heme groups that can act as electron transfer mediators and are exposed on the outermost membrane of the cell . Moreover, the culture of heme‐depleted cells has recently revealed that c‐ type cytochromes are the key for the interchange of electrons with an electrode . Therefore, the redox chemistry of Geobacter is mainly based on the chemistry of the heme group, which hosts an iron atom that can be reversibly reduced or oxidized.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that cytochromes were localized to the outer membrane of the anaerobically grown cells of Shewanella and facilitated electron transfer from intact bacterial cells to electrodes (29, 35). One study also demonstrated that c -type cytochromes were essential for extracellular electron transfer by G. sulfurreducens and its electron-transferring ability depended on the content of cytochrome C (15). Thus, the results of the Raman microscopy analysis provided additional support along with the CV analysis for strain SCS5 being a potent electrochemically active bacterium.…”
Section: Discussionmentioning
confidence: 99%
“…0 V) in contrast with the typical value of ca. 0.2 V detected on standard graphite electrodes [7,36]. The shift in the oxidation potential might be related with graphene's better electric conductivity, which is several orders of magnitude higher than that of carbon [33].…”
Section: Screen-printed Electrodes (Spes): Testing Electroactivity Inmentioning
confidence: 94%